Development of Mushroom E-Brochure as a Learning Resource for Class X to Improve Representation Ability (FMIPA UNNES, 2022)
Result of observations and interviews with class X biology teachers at SMA Institut Semarang, mushroom material is one of the materials that are quite difficult, complex and abstract for students to learn and understand because mushroom material has scientific names that students must understand, like divisions that are almost the same shape. In terms of representation ability, students still struggle to draw mushrooms, so they cannot distinguish mushrooms according to their division. This study aims to develop, test the feasibility and improve students' representational abilities by using e-brochures as a learning resource. This study is a Research and Development (R&D) and was tested using a one-shot case study design. The research goes through the stages of identifying potentials and problems, collecting data, designing products, expert validation, product revisions, small-scale trials, revisions, and large-scale trials so that the final product is produced. The results showed that the e-brochure was feasible to use with a percentage of material eligibility of 77.5%, media eligibility of 78.5% with appropriate criteria, and product responses of 91.55% with very legible standards. The ability of representation can be seen with the results of the t-test 0.000 <0.05 using SPSS, so it can be concluded that there is a significant difference between the results of the pre-test and post-test. The increase in N-gain of pre-test and post-test data was obtained by 70% with high criteria. Based on these results, it can be concluded e-brochure as a learning resource for class X to improve representation ability is feasible to use, and the response of e-brochure is very legible. Suggestions for further research are the development of mushroom e-brochures as a learning resource for class X to improve representation skills associated with other materials.